A study on mobile phone ownerships and pattern of use among working adults, Sibu - Wan, Ching Ching (Universiti Malaysia Sarawak (UNIMAS), 2009)
MObile phone, which was introduced slightly more than a decade ago, is an item which is carried by practically anyone these days. The phone is no longer just a tool for voice communication. Producers of mobile phones are competing for the market not just on the prices but features or function as well. New models come into the market with new features at unbelievable frequenciey How do customers decide what brand or what kind of mobile phone to purchase? How much of the applications available on their mobile phone do they use? In this cross-sectional study of mobile phone users in Sibu Town, a sample size of 300 was set and the sample selection was through a convenient sampling method. A total of 246 respondents took part. Interviews using questionnaires were employed. Fifty six and half(56.5%) percent and 43.5% were female and male respectively. The most popular provider was Celcom (37%), followed by Digi (28.9%) and Maxis (11 %). The most popular brand was Nokia (51 %), Sony Ericsson (27 or 11 %), and Samsung (17 or 6.9%). Based on this scoring system the most popular application was Short Messaging Service (SMS) . This was followed by the use of Camera (47%), Reminder (45%), Bluetooth (37%), MP3 (36%), Games (32%), MMS (22%), Downloading (21 %), Infrared (19%), Radio (18%), Subscription (15%), Fun Voice (15%), Mobile TV (13%), Surfing Internet (13%), Emailing (11 %), Navigation (11 %), 3G (9%), WiFi (7%) and Reading PDF File (5%). The users in Sibu seem to have positive attitude towards this technology. It is quiet obvious that they found this technology useful in their life. This study concludes, among others, that the Mobile phone is no longer a sign of wealth or status symbol. It is a gadget which is important in daily lives ofeveryone.